(untitled) (International Journal of Engineering and Computer Science, 2014)
It is an increasing demand of high bandwidth and high data rate without loss of any information in any communication system. To meet almost all the requirements optical communication system is preferable. For long distance transmission optical amplifiers such as Erbium doped fiber amplifier (EDFA), Semiconductor Optical amplifier (SOA), Raman Amplifier, Parametric Amplifier etc. are being used at the receiver side. It is a very important that parameter of these amplifier are analyzed such a way that it can perform better for the specific optical communication application. Pumping scheme at receiver side is also a potential candidate for the ‘last mile’ transmission. In this paper performance of Erbium doped fiber amplifier for parameters like Bit rate, Bit Error rate, fiber length, Signal to Noise ratio (SNR), Q-factor, gain, Noise figure are analyzed in optsim5.0 software environment in L-band 1520-1610 nm range and for higher bit rate to get optimum signal at receiver side and also the effect of changing various parameters on system performance have been shown to improve the efficient optical communication.